Progression of dementia symptoms in old patients because of confinement in the COVID-19 pandemic era: challenges for mental health workers and caregivers - Ria Maria Theresa; Putri Nugraheni; Attaufiq Irawan; Muhammad Ariq Fiqih (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Currently, the whole world is experiencing a COVID-19 pandemic. The elderly are one of the populations with a high physical and mental risk of being affected by covid-19. Dementia is a psychiatric disorder that is often experienced by the elderly. We describe two cases of dementia that occurred during the COVID-19 pandemic situation. Both cases explain the condition of dementia patients during quarantine due to the implementation of the PSBB (confinement). Dementia patients have difficulty in understanding and complying with health protocols. The emergence of exacerbation symptoms and education on health protocols are challenging for caregivers during the COVID-19 pandemic. The role of mental health workers is important to help caregivers understand the causes of worsening symptoms of dementia patients because of changes in environmental conditions during the COVID-19 pandemic situation and provide examples for caregivers on how to educate patients with appropriate health protocols. Modification of activities during a pandemic and regular communication with caregivers can be a solution to addressing challenges.